Дослідження характеристик рухливості легкоброньованої колісної військової машини з гідромеханічною трансмісією - Борисюк, М. Д.; Толстолуцький, В. О.; Стрімовський, С. В.; Соловйов, В. М. (НТУ "ХПІ", 2010)
Complex mathematical model of wheel vehicle with automatic transmission is offered at the article. Due to usage of offered mathematical model complex numerical experiment was organized. It allowed to define the mobility features of the vehicle and quality of control system algorithm work before the pilot model was created.
Keywords: колісні машини; двигун; вихідний вал; система керування; рух машини; гусеничні машини